Production of neutralizing human monoclonal antibody directed to tetanus toxin in CHO cell - Chin, J; Sohn, Y; Lee, SH; Park, YI; Choi, MJ (ACADEMIC PRESS LTD ELSEVIER SCIENCE LTD, 2003)
By the fusion of lymphocytes from hyperimmunized people with heteromyeloma cells, 600 human hybridoma cell lines were generated. Even though seven cell lines produced antibodies against tetanus toxoid, only two antibodies from hybrid CH8 and CH5 only neutralized the tetanus toxin and completely protected the mice that had been challenged with the toxin even at the level of 90 mean lethal dose. The cDNA of light (L) chain and heavy (H) chain variable region was isolated,and then inserted into expression vectors containing human IgG constant regions. After transfection of the recombinant human IgG gene into Chinese Hamster Ovary (CHO) cells, transformants secreting the complete human antibody were selected. The recombinant human antibodies produced from CHO cells possessed neutralizing activity against tetanus toxin just like the original human antibodies produced from human hybridoma cell lines. Western blot analysis showed that rCH8 and rCH5 antibodies recognized the H chain of tetanus toxin and did not bind to its L chain. The neutralizing test showed that HmAb rCH5 had 4.55 IU and HmAb rCH8 had 1.09 IU/100 mug of IgG, respectively. Mixing of the two HmAbs resulted in synergistic effects. On a weight basis (IU/100 mug IgG), the highest potency values were obtained when the two HmAbs were combined in equal quantity. The neutralizing activity of rCH8 and rCH5 mixture was 6.94 IU/ 100 mug IgG. (C) 2003 The International Association for Biologicals. Published by Elsevier Science Ltd. All rights reserved.
Keywords: LINKED-IMMUNOSORBENT-ASSAY; PROTECTION; EPITOPES; MOLECULE; BINDING